2006
DOI: 10.1007/s10681-006-9315-0
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of the tepal colour of Begonia x tuberhybrida Voss. for DUS testing using image analysis

Abstract: In the framework of variety testing, evaluation of the flower of Begonia x tuberhybrida Voss. is done by experts. The colours of the flowers are compared with the RHS colour chart. For each flower colour a code is given. This method has several disadvantages (data cannot be statistically analyzed with standard ANOVA techniques, bias by the expert is possible, difficult measurement depending on the light environment,...) that can be overcome with image analysis. In this study several parameters were tested to d… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
8
0

Year Published

2008
2008
2023
2023

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 11 publications
(8 citation statements)
references
References 10 publications
(8 reference statements)
0
8
0
Order By: Relevance
“…Grain number is a 'bad' feature, the reason may be that most of the peanuts we chose are double kernel, and the difference is not significant in grain number. Furthermore, for area (1), extent (8), smoothness (14), consistency (16), area/convex area (11), perimeter (4), eccentricity (7), shape factor (9), their discrimination abilities are high, and they can also be used as potential traits for DUS testing in the future. Here, we have chosen these 12 features for DUS testing as candidate features.…”
Section: Feature Selection By Fishermentioning
confidence: 99%
See 2 more Smart Citations
“…Grain number is a 'bad' feature, the reason may be that most of the peanuts we chose are double kernel, and the difference is not significant in grain number. Furthermore, for area (1), extent (8), smoothness (14), consistency (16), area/convex area (11), perimeter (4), eccentricity (7), shape factor (9), their discrimination abilities are high, and they can also be used as potential traits for DUS testing in the future. Here, we have chosen these 12 features for DUS testing as candidate features.…”
Section: Feature Selection By Fishermentioning
confidence: 99%
“…By investigating its germplasm resources we found that this variety is a breed after hybridization between Baisha 1016 and 99D1, and belongs to a Spanish type small peanut which is different from other big peanut varieties. Beside this, the varieties numbered 7, 10, 11,12,8,14,13 are gathered into the second major category and the rest are divided into the third category. The varieties of the second category were mainly harvested from Qingdao, China and it may be due to external environmental factors that make this category exhibit same characteristics in appearance.…”
Section: Paternity Analysis By K-meansmentioning
confidence: 99%
See 1 more Smart Citation
“…(Yoshioka et al, 2006)], and begonia [Begonia •tuberhybrida Voss. (Lootens et al, 2007)]. Digital color analysis is also performed in plant pathology to quantify lesions on diseased leaves (Kwack et al, 2005).…”
mentioning
confidence: 99%
“…But since the aperture of many colorimeters is limited in size and shape, it is difficult to accurately evaluate fruit that has an uneven surface colour, such as gradations, blotches, and stripes. However, recent improvements in computer and optical instrument performance may allow researchers to develop new objective methods of phenotyping plant organ colours based on image analysis (e.g., Choi et al 1995;Leemans et al 2002;Yoshioka et al 2006Yoshioka et al , 2007Lootens et al 2007;Darrigues et al 2008). In many cases, simple statistics, such as averages and standard deviations of the RGB (red, green, blue) colour channels or of the CIE-Lab (L*, a*, b*) colour space, are calculated as colour features of an object or region of interest (ROI).…”
Section: Introductionmentioning
confidence: 99%